Protestant Dissent and Philanthropy in Britain, 1660-1914 - Binfield, Clyde (Studies in Modern British Religious History Ser., 2019)
Philanthropy was an essential feature of the relationship between Dissent and the society from which it sometimes felt itself to be separate.